Understanding Why Children Commit Scale Errors: Scale Error and Its Relation to Action Planning and Inhibitory Control, and the Concept of Size - Ishibashi, Mikako; Moriguchi, Yusuke (Frontiers in Psychology, 2017)
Scale error is a phenomenon where young children attempt to perform inappropriate actions on miniature object without considering the actual size of the object. The present study examined two hypotheses on what factors contribute to the occurrence of scale errors, focusing on the following possible factors: action planning and inhibitory control, and concept of size. Thus, we hypothesize that scale errors derived from either immaturity of their action planning and inhibitory control abilities or understanding of size concepts. The results revealed that the concept of size was significantly negatively associated with the occurrence of scale errors. However, action planning and inhibitory control were not significantly associated with the occurrence of scale errors. These results suggest that scale errors may arise from a misunderstanding of size concepts.